PENGARUH PENAMBAHAN NaNO3 DAN K2HPO4 PADA MEDIA BG-11 TERHADAP KONSENTRASI BIOMASSA DAN KLOROFIL Tetraselmis chuii - Puspita Swandewi, I Gusti Ayu Putu Agung; Dewi Anggreni, A. A. Made; Admadi H, Bambang (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 5 No 1 (2017): Maret)
The aims of this study were to know the effect of addition of NaNO3 and K 2HPO4 on BG-11 medium on biomass and chlorophyll concentration of  Tetraselmis chuii  and to fine out the best concentration of  NaNO3 and K 2HPO4 on BG-11 medium to produce highest biomass and chlorophyll concentration of Tetraselmis chuii. This study used a factorial randomized block design. The first factor was  NaNO3 consists of three levels i.e. 0.5, 1.5 and 2.5 g/l. The second factor was K2HPO4 consists of three levels i.e. 0.020, 0.035 and 0.050 g/l.  The experiments were grouped into 2  groups based on the  time of culturitation, in order to obtain 18 experimental units.  Data were analyzed by analysis of variance and if the treatment significantly affected the parameter followed by Duncan test. The result showed that addition of NaNO3 and K 2HPO4 had very significant effect on the concentration of biomass and chlorophyll content of  Tetraselmis chuii.  The addition of NaNO3 1.5 g/l and  K2HPO4 0.035 g/l was produce the highest of biomass and chlorophyll concentration of 3.3 x 10 6 cells/ml and 10.17 mg/g, respectively. Keywords : biomass, chlorophyll, K2HPO4 , NaNO3 , Tetraselmis chuii.
Keywords: 124,